2021
DOI: 10.1159/000516922
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Fecal Microbiota in Left-Side and Right-Side Human Colorectal Cancer

Abstract: <b><i>Introduction:</i></b> Microbiomes play a vital role in the development and progression of cancer. The clinical status, including prognosis, genetic mutations, and sensitivity to chemotherapy, differs depending on the location of colorectal cancer (CRC); however, the association between gut microbiota and the location of CRC is not entirely understood. This study was conducted to evaluate the differences in the gut microbiota in patients with CRC according to the location of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In addition, Fusobacterium nucleatum is associated with tumorigenesis in colorectal cancer [16]. Furthermore, the microbiome differs in left-and right-side colorectal cancer [17,18]. The challenge of distinguishing whether certain bacteria have a selective advantage due to cancer, and are therefore more detectable in cancer patients, or whether certain bacteria promote cancer development remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fusobacterium nucleatum is associated with tumorigenesis in colorectal cancer [16]. Furthermore, the microbiome differs in left-and right-side colorectal cancer [17,18]. The challenge of distinguishing whether certain bacteria have a selective advantage due to cancer, and are therefore more detectable in cancer patients, or whether certain bacteria promote cancer development remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One cohort study reported that the genus Holdemanella was enriched in Tibetan Highlanders suffering from coronary artery disease compared with healthy Tibetan Highlanders and Han coronary artery disease patients living at high and low altitudes (32). Several other studies have also found that Holdemanella was significantly increased in patients suffering from autism spectrum disorder, colorectal cancer, or chronic kidney disease (33)(34)(35). The differences in the results reaffirmed the challenge of distinguishing a FIGURE 6 | Associations between microbial pathways and multiple factors.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, that association had a pleiotropic effect, that is, rather than the presence of Firmicutes affecting the risk of CRC (cause and effect), there is a shared genetic component that affects both (common biologic mechanism). It has been described the importance of the microbiota in CRC risk and development [ 66 , 67 ], the differences in its composition between left and right colon cancer [ 68 , 69 , 70 ] and shared genetic variants in CRC risk and the abundance of Firmicutes [ 13 ]. Although the connection we have detected between CRC and Firmicutes is based only on their shared genetic variants, it has been observed that the involvement of Firmicutes in CRC risk was variable [ 68 , 69 , 70 , 71 ]: some genera of Firmicutes were enriched in CRC while others were depleted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described the importance of the microbiota in CRC risk and development [ 66 , 67 ], the differences in its composition between left and right colon cancer [ 68 , 69 , 70 ] and shared genetic variants in CRC risk and the abundance of Firmicutes [ 13 ]. Although the connection we have detected between CRC and Firmicutes is based only on their shared genetic variants, it has been observed that the involvement of Firmicutes in CRC risk was variable [ 68 , 69 , 70 , 71 ]: some genera of Firmicutes were enriched in CRC while others were depleted. In the case of Cyanobacteria, a higher abundance of that phylum has been observed in colorectal adenomas [ 72 ], and in animal models, it has been observed a higher abundance of Cyanobacteria when oxaliplatin is administered [ 73 ].…”
Section: Discussionmentioning
confidence: 99%